Physiological Features of the Response of the Respiratory and Circulation Systems to Physical Load in Students Engaged in Winter Soccer - Kapilevich L. V. Leonid Vladimirovich; Ilyin A. A. Aleksandr Aleksandrovich; L. Jiao; F. Xiao; Krivoshchekov S. G. Sergey Georgievich (2024, 2024)
Title screen